Implikasi Hukum Risalah Fiktif Akta Pernyataan Keputusan Rapat Terhadap Upaya Hukum Pemulihan Jabatan Notaris - Gosan, John Tiel; Rasji, Rasji (Universitas Ekasakti, 2023)
The purpose of writing this article is to find out the legal implications of fictitious minutes of the deed of statement of meeting decisions on legal efforts to restore the position of notary. This article uses normative legal research, with a statute approach and conceptual approach and descriptive qualitative research analysis with deductive thinking method. The legal implications of making fictitious minutes of the deed of meeting decision statement can be in the form of civil violations with the implication that the deed of meeting decision statement is declared cancelled and the notary will bear the material losses incurred, then the Notary can be charged with a crime, namely in the falsification of document data with the implication of imprisonment, and the last is charged with the code of ethics of the notary position which has implications for reprimands to dishonorable dismissal from the position of notary by the Ministry of Law and Human Rights as having the authority to appoint and dismiss notaries. The legal remedies that can be taken by notaries can only be done for violations of the code of ethics, namely by filing an objection or administrative appeal against the decision of the Ministry of Law and Human Right.